1999
DOI: 10.1001/jama.281.20.1927
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Trials Comparing β-Blockers, Calcium Antagonists, and Nitrates for Stable Angina

Abstract: beta-Blockers provide similar clinical outcomes and are associated with fewer adverse events than calcium antagonists in randomized trials of patients who have stable angina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
91
0
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(98 citation statements)
references
References 91 publications
1
91
0
6
Order By: Relevance
“…Those ligands are known as inverse agonist, given that they have the opposite effect of agonists. Therefore, b-antagonists are used clinically to reduce heart rate and force of contraction in hypertension, angina and acute myocardial infarction by direct blocking endogenous catecholamine activity, [11][12][13] implying that inverse agonists may have preferred therapeutic applications in the pathophysiology of several cardiovascular diseases.In all seven transmembrane helix (TMH) of GPCRs it appears that the general mechanism of activation involves disruption of intramolecular constraints, leading to TMH movement and formation of new interactions, which stabilize the active state of the receptor. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] The aspartic acid at position 104 in TMH II of the human b 1 -AR is conserved in all b-adrenergic 28-31) , a-adrenergic receptor 32) and also muscarinic cholinergic receptors, [33][34][35] which may take part in an ionic interaction with amino group containing catecholamines, whose disruption of interaction makes the receptor active conformation state.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Those ligands are known as inverse agonist, given that they have the opposite effect of agonists. Therefore, b-antagonists are used clinically to reduce heart rate and force of contraction in hypertension, angina and acute myocardial infarction by direct blocking endogenous catecholamine activity, [11][12][13] implying that inverse agonists may have preferred therapeutic applications in the pathophysiology of several cardiovascular diseases.In all seven transmembrane helix (TMH) of GPCRs it appears that the general mechanism of activation involves disruption of intramolecular constraints, leading to TMH movement and formation of new interactions, which stabilize the active state of the receptor. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] The aspartic acid at position 104 in TMH II of the human b 1 -AR is conserved in all b-adrenergic 28-31) , a-adrenergic receptor 32) and also muscarinic cholinergic receptors, [33][34][35] which may take part in an ionic interaction with amino group containing catecholamines, whose disruption of interaction makes the receptor active conformation state.…”
mentioning
confidence: 99%
“…Those ligands are known as inverse agonist, given that they have the opposite effect of agonists. Therefore, b-antagonists are used clinically to reduce heart rate and force of contraction in hypertension, angina and acute myocardial infarction by direct blocking endogenous catecholamine activity, [11][12][13] implying that inverse agonists may have preferred therapeutic applications in the pathophysiology of several cardiovascular diseases.…”
mentioning
confidence: 99%
“…Even in the absence of perceived and absolute contraindications, the use of β-blockers in patients with established CAD remains low 3. In a large meta-analysis, β-blockers were found to have similar efficacy to calcium channel blockers for angina relief, but were associated with fewer adverse events 4. Potential side effects of β-blockers include impaired sexual function, reduced exercise capacity, bradycardia and generalised fatigue.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…Available meta-analysis of randomised and crossover trials comparing BBs, CCBs and nitrates suggested that BBs provide similar clinical outcomes and are associated with fewer adverse events (AEs) than CCBs for patients with stable angina pectoris 4. Meta-analysis of efficacy of monotherapy compared with combined antianginal drugs for treating stable angina pectoris suggested that the combined therapy with CCBs and BBs is more effective than monotherapy 5.…”
Section: Introductionmentioning
confidence: 99%